PEDAGOGÍA INTERCULTURAL SUMAK WAWAKUNA (LINDOS NIÑOS) EN EL DESARROLLO DEL LENGUAJE ORAL DE SU LENGUA MATERNA (KICHWA) Y EN EL ESPAÑOL DE LOS NIÑOS Y NIÑAS DEL CIBV “ABDÓN CALDERÓN” DEL CANTÓN GUANO, DURANTE EL PERÍODO DICIEMBRE 2017 - MAYO 2018. - Bermeo, Sandra Jimena (2019)
The present research work entitled “Intercultural Pedagogy Sumak Wawakuna (lindos ninos) in the development of the oral language of their mother tongue (Quichua) and in the Spanish of the children of the CIBV "Abdon Calderon" of Guano canton, during the period December 2017 - May 2018” It was derived from the problem detected in the Pulingui community, that corresponded to the poor development of the oral language of the mother tongue (Quichua) since the practice of this language was discontinued from parents to their children who were at an early age, time in which the greatest amount of vocabulary is acquired. This caused a linguistic impoverishment, so it was decided to propose this research that had as objective the elaboration and application of an intercultural methodological guide for the educators that work in the CIBV whose main contribution of texts and activities were created by the researcher. The general objective of this research was to develop the oral language of their mother tongue (Quichua) and in Spanish in the children from one to three years of age of the CIBV (Centro Infantil del Buen Vivir). The methodology was supported by a non-experimental design.The types of research correspond to a descriptive, field and quantitative process, the deductive method was applied. The sample consisted of 36 children to whom were applied techniques and instruments based on observation indicators and checklist. Within the presentation and discussion of results, the use of the Intercultural guide sumak wawakuna (lindos ninos) serves as support to educators with activities in weekly planning to develop oral language in both languages in children. Therefore, we can concluded that the sumak wawakuna intercultural guide with their proposed activities, helped the children to increase the development of oral language in both languages.